Preparation of PCL Electrospun Fibers Loaded with Cisplatin and Their Potential Application for the Treatment of Prostate Cancer - Hilla Mills; Ronald Acquah; Nova Tang; Luke Cheung; Susanne Klenk; Ronald Glassen; Magali Pirson; Alain Albert; Duong Trinh Hoang; Thang Nguyen Van (Emergency Medicine International)
Prostate cancer is a global fatal type of cancer. It is a type of cancer that affect men. Signs and symptoms of the disease include blood in the urine, pain when one micturates, and difficulties in penis erection. Cisplatin chemotherapy is a principal treatment normally given to the prostate cancer patients. Nonetheless, on its own, cisplatin loses efficacy once administered due to liver pass effects and other biochemical attacks. In this paper, we looked at preparation of PCL nanoparticles loaded with cisplatin and their potential for the treatment of prostate cancer. PCL nanoparticles protect cisplatin from biochemical attack, thus increasing drug efficacy. Incorporation of P-glycoprotein inhibitors in PCL nanoparticles (NPs) loaded with cisplatin could improve prostate cancer treatment even more.